Consumer protection on online transactions in Kurdistan: Lessons from Malaysian law - Amin, Kawa Akram Mohammed (2014)
Recently, the increase in the usage of e-commerce has been one of the most significant developments of business sector. It has transformed many marketplaces to start new opportunities have never been imagined before. Kurdistan is considered as one of the very few regions in the world that are still so far from the real use of inevitable services of e-commerce. Primarily, Kurdistan suffers various features that run as barriers to an effective use of e-commerce, such as inadequate laws to protect consumers electronically, lack of awareness and understanding the benefits of electronic commerce, lack of information and communication technologies (ICT) knowledge and skills, unstable physical network infrastructure, security and other problems related to costs for the adoption of a new technology. This study aims to identify potential issues and problems facing e-commerce in Kurdistan. For this purpose, the study has conducted a comparison between both Malaysian and Kurdish contexts in terms of consumer protection law on online transactions. This study also indicates the intention of Kurdish government to apply Malaysian context into its national laws in terms of e-transactions. As a part of data collection, this study has conducted two versions of formal and informal interviews involved three sets of questions asked each group of selected panelists from governmental and nongovernmental organizations in Kurdistan. The given discussions by this study focused on the technological and law issues that could drive e-commerce in this region. Suggestions were given for better improvement of Kurdish internet laws to provide safe electronic environment and to bring Kurdistan amongst other developing countries to become an active member in the digital economy.